Small Scale Direct Potable Reuse (DPR) Project for a Remote Area - Jianhua Zhang; Mikel Duke; Kathy Northcott; Michael Packer; Mayumi Allinson; Graeme Allinson; Kiwao Kadokami; Jace Tan; Sebastian Allard; Jean-Philippe Croué; Adrian Knight; Peter Scales; et al. (Water, 2017)
An Advanced Water Treatment Plant (AWTP) for potable water recycling in Davis Station Antarctica was trialed using secondary effluent at Selfs Point in Hobart, Tasmania, for nine months. The trials demonstrated the reliability of performance of a seven barrier treatment process consisting of ozonation, ceramic microfiltration (MF), biologically activated carbon, reverse osmosis, ultra-violet disinfection, calcite contactor and chlorination. The seven treatment barriers were required to meet the high log removal values (LRV) required for pathogens in small systems during disease outbreak, and on-line verification of process performance was required for operation with infrequent operator attention. On-line verification of pathogen LRVs, a low turbidity filtrate of approximately 0.1 NTU (Nephelometric Turbidity Unit), no long-term fouling and no requirement for clean-in-place (CIP) was achieved with the ceramic MF. A pressure decay test was also reliably implemented on the reverse osmosis system to achieve a 2 LRV for protozoa, and this barrier required only 2–3 CIP treatments each year. The ozonation process achieved 2 LRV for bacteria and virus with no requirement for an ozone residual, provided the ozone dose was >11.7 mg/L. Extensive screening using multi-residue gas chromatography–mass spectrometry (GC–MS) and liquid chromatography–mass spectrometry (LC–MS) database methods that can screen for more than 1200 chemicals found that few chemicals pass through the barriers to the final product and rejected (discharge) water streams. The AWTP plant required 1.93 kWh/m3 when operated in the mode required for Davis Station and was predicted to require 1.27 kWh/m3 if scaled up to 10 ML/day. The AWTP will be shipped to Davis Station for further trials before possible implementation for water recycling. The process may have application in other small remote communities.